Construction of a novel miRNA regulatory network and identification of target genes in gestational diabetes mellitus by integrated analysis - Ding, Liyan; Shen, Yi; Wang, Anqi; Lu, Changlian; Gu, Xuefeng; Jiang, Liying (Frontiers in Genetics, 2022)
Backgrounds: Given the roles of microRNA(miRNA) in human diseases and the high incidence of gestational diabetes mellitus(GDM), the aim of the study was to examine miRNA signatures and crucial pathways, as well as possible biomarkers for GDM diagnosis. Methods: We conducted a two-stage study to explore functional miRNA and those target genes. Twelve participants(6 GDM and 6 non-GDM) were first enrolled and performed RNA sequencing analysis. The overlapped candidate genes were further screened in combination with differentially expressed genes(DEGs) of GEO datasets(GSE87295, GSE49524 and GSE19649) and potential target genes of DEMs. Candidate genes, critical pathways, small molecular compounds and regulatory networks were identified using bioinformatic analysis. The potential candidate genes were then investigated using the GEO dataset(GSE103552) of 19 participants in the validation stage(11 GDM and 8 non-GDM women). Results: Briefly, blood samples were sequenced interrogating 50 miRNAs, including 20 up-regulated and 30 down-regulated differentially expressed microRNAs(DEMs) in our internal screening dataset. After screening GEO databases, 123 up-regulated and 70 down-regulated genes were overlapped through DEGs of GEO datasets and miRNA-target genes. MiR-29b-1-5p-TGFB2, miR-142-3p-TGFB2, miR-9-5p-FBN2, miR-212-5p-FBN2, miR-542-3p-FBN1, miR-9-5p-FBN1, miR-508-3p-FBN1, miR-493-5p-THBS1, miR-29b-3p-COL4A1, miR-432-5p-COL5A2, miR-9-5p-TGFBI, miR-486-3p-SLC7A5 and miR-6515-5p-SLC1A5 were revealed as thirteen possible regulating pathways by integrative analysis. Conclusions: Overall, thirteen candidate miRNA-target gene regulatory pathways representing potentially novel biomarkers of GDM diseases were revealed. Ten chemicals were identified as putative therapeutic agents for GDM. This study examined a series of DEGs that are associated with epigenetic alternations of miRNA through an integrated approach and gained insight into biological pathways in GDM. Precise diagnosis and therapeutic targets of GDM would be further explored through putative genes in the future.